Sistem Kendali Pengatur Suhu Ruangan pada Smart Building dengan Aplikasi Telegram menggunakan Fuzzy Logic Control - Syafii, Abdullah; Mursito, Agung; Muhlisin, Ahmad; Widiarto, Andi; Saifudin, Aries; Nirmala, Endar (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Rapid technological advances have resulted in many changes that occur in everyday life, this arises from the existence of creative ideas combined with things that are around and existing technological developments. For example, in regulating room temperature, namely adjusting the temperature in an air conditioner so that it can be used efficiently. This room temperature controller is basically done manually by adjusting the temperature according to the needs of the room. Basically, for temperature regulation, the principle of adding or subtracting degrees to the temperature control device is used. This is done manually by humans, so if there are many rooms that are required to use the room temperature control device, it takes a lot of time and calm to be issued. From this, an idea emerged to create a room temperature control system that could be controlled using the Telegram application. In this case, the fuzzy logic method is used to perform data presentation and processing in combination with the Raspberry PI microcontroller. According to the test results, humidity and temperature in the room can be captured correctly, and the system can regulate humidity and temperature in each room in the building through the Telegram application, so that it can overcome the problem of inefficient room temperature regulation.